(untitled) (International Journal of Engineering and Computer Science, 2015)
Cloud computing is a rising computing standard in which assets of the computing framework are given as a service over the Internet. It delivers new challenges for data security and access control when clients outsource sensitive data for offering on cloud servers. These results unavoidably present a substantial processing overhead on the data possessor for key distribution and data administration when fine-grained data access control is in demand, and subsequently don’t scale well. The issue of at the same time accomplishing fine-graininess, scalability, and data confidentiality of access control really still remains uncertain. The system characterize and implements access policies based on data qualities, and, then again, permits the data owner to represent the majority of the calculation included in fine-grained data access control to un-trusted cloud servers without unveiling the underlying data substance. This can be achieved by exploiting and combining techniques of decentralized key policy Attribute Based Encryption (KP-ABE). The proposed approach is highly efficient and secure. Also Data deduplication is one of important data compression techniques for eliminating duplicate copies of repeating data, and has been widely used in cloud storage to reduce the amount of storage space and save bandwidth. To protect the confidentiality of sensitive data while supporting deduplication, the convergent encryption technique has been proposed to encrypt the data before outsourcing it also represents several new deduplication constructions supporting authorized duplicate check in hybrid decentralized cloud architecture.